Deadly Professions: Violent Attacks Against Aid-Workers and the Health Implications for Local Populations - Jason-Louis Carmichael; Mohammad Karamouzian (Kerman University of Medical Sciences, 2014)
War has devastating implications for families, communities, cultures, economies, and state infrastructure. Similarly, the last decade has seen an increase in the number of attacks against health workers in conflict zones and unstable environments. Unfortunately, these attacks have grave consequences for local populations which often rely on foreign aid programs for their health and well-being. As such, this paper will examine why aid-workers have increasingly been targeted for abductions, ambushes, assassinations, and various forms of intimidation. Furthermore, examples of terminated health programs, as well as populations served by current medical and humanitarian interventions, will be provided to impart a sense of magnitude and importance of health programs to the reader. Lastly, suggestions will be presented which could serve to minimize aid-workers' risk and exposure to acts of violence in the field.